2018
DOI: 10.1098/rspb.2018.0231
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of inbreeding on reproductive senescence

Abstract: Inbreeding depression plays a significant role in evolutionary biology and ecology. However, we lack a clear understanding of the fitness consequences of inbreeding depression. Studies often focus on short-term effects of inbreeding in juvenile offspring, whereas inbreeding depression in adult traits and the interplay between inbreeding depression and age are rarely addressed. Inbreeding depression may increase with age and accelerate the decline in reproductive output in ageing individuals (reproductive senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…For example, if inbreeding depression was caused by genes affecting energy metabolism (46), environmental factors, such as extreme weather phenomena, could be expected to mediate even stronger inbreeding depression (26). On the other hand, the strength of inbreeding depression caused by genes affecting intrinsic factors, such as sperm (47) or egg quality (48,49), would likely be less affected by the environment. Nevertheless, laboratory studies have shown that inbreeding depression can be more severe under stress caused by extrinsic factors, such as heat and intraspecific competition, than under benign environmental conditions (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if inbreeding depression was caused by genes affecting energy metabolism (46), environmental factors, such as extreme weather phenomena, could be expected to mediate even stronger inbreeding depression (26). On the other hand, the strength of inbreeding depression caused by genes affecting intrinsic factors, such as sperm (47) or egg quality (48,49), would likely be less affected by the environment. Nevertheless, laboratory studies have shown that inbreeding depression can be more severe under stress caused by extrinsic factors, such as heat and intraspecific competition, than under benign environmental conditions (27).…”
Section: Discussionmentioning
confidence: 99%
“…Our B estimate in adult male longevity was substantially higher than that for adult female longevity. Sexspecific differences in inbreeding depression have been found in a variety of species, including in captive canaries (Serinus canaria, 50 ) as well as wild song sparrows 51 . Senescence theory predicts that individuals that live longer will experience greater inbreeding depression due to weaker selection against late-acting deleterious alleles 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…While there are several evolutionary theories explaining inbreeding depression and senescence, the dominant theories are based on the effects of spontaneous mutations with deleterious effects in both cases 27 , 28 , suggesting that inbreeding depression and senescence can interact. Many studies have empirically shown a positive interaction between the two phenomena, with greater inbreeding depression at older ages 6 , 23 , 25 , 26 , 28 30 , 89 , even if some studies did not find this relationship 90 , 91 .…”
Section: Discussionmentioning
confidence: 99%
“…According to senescence theories, the progressive decline in performance with age can be caused by an accumulation of deleterious mutations (mutation accumulation theory) and/or an accumulation of alleles that are beneficial at young ages but have deleterious effects at old ages (antagonistic pleiotropy theory) 21 and/or a trade-off among growth, reproduction and DNA repair maintenance (disposable soma theory) 21 , 24 . Since senescence increases individual sensitivity to intrinsic and extrinsic factors 20 , it has the potential for significant interaction with inbreeding and adaptation to captivity 25 , 26 . Indeed, some theories describing senescence are based on the assumption that natural selection against deleterious alleles decreases with age 27 , thus, it is expected that changes in natural selection in captivity can lead to an alteration in individual senescence trajectories.…”
Section: Introductionmentioning
confidence: 99%